2002
DOI: 10.1046/j.1365-2249.2002.01833.x
|View full text |Cite
|
Sign up to set email alerts
|

Defective expression and tyrosine phosphorylation of the T cell receptor zeta chain in peripheral blood T cells from systemic lupus erythematosus patients

Abstract: SUMMARYWe have reported that tyrosine phosphorylation and expression of the T cell receptor zeta chain (TCR z ) was decreased in two systemic lupus erythematosus (SLE) patients with an abnormal TCR z lacking exon-7. To examine further the TCR z defect and any possible relationship with specific clinical features, we studied the expression of TCR z in peripheral blood T cells from 44 patients with SLE, 53 with other rheumatic diseases (30 rheumatoid arthritis (RA), 11 systemic sclerosis (SSc) and 12 primary Sjö… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 61 publications
(62 reference statements)
0
41
0
Order By: Relevance
“…In line with this, defects in CD3z expression/ function were suggested to have implications for the development of human autoimmune phenotypes (24,35,36). Thus, several groups reported altered expression and function of CD3z in patients with SLE (19,20) or rheumatoid arthritis (21,22). Moreover, familybased association studies of SLE showed that polymorphisms in the CD3z 39-untranslated region are associated with defective CD3z expression in SLE patients (37).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In line with this, defects in CD3z expression/ function were suggested to have implications for the development of human autoimmune phenotypes (24,35,36). Thus, several groups reported altered expression and function of CD3z in patients with SLE (19,20) or rheumatoid arthritis (21,22). Moreover, familybased association studies of SLE showed that polymorphisms in the CD3z 39-untranslated region are associated with defective CD3z expression in SLE patients (37).…”
Section: Discussionmentioning
confidence: 92%
“…Ras is a GTPase upstream of the MAPK cascade pathway, and its activity is dependent on phosphorylation of CD3z and ZAP-70. In humans, a defective expression of the CD3z-chain has been associated with autoimmune diseases, including systemic lupus erythematosus (SLE) (19,20) and rheumatoid arthritis (21,22), with T cells from these patients displaying a functional impairment. Together, these data suggest that downregulation of CD3z has functional consequences in systemic autoimmunity (23,24).…”
mentioning
confidence: 99%
“…In T cells obtained from peripheral blood of subjects with the autoimmune disease systemic lupus erythematosus, defective expression and tyrosine phosphorylation of the TCR chain has been reported (35)(36)(37). The molecular mechanisms of expression and phosphorylation defects in the TCR chain may involve distinct DNA sequences in the 3Ј UTR of the CD247 gene encoding TCR .…”
Section: Discussionmentioning
confidence: 99%
“…Cells were lysed with the lysis buffer and disrupted by sonication according to a previously described method (19). After centrifuging at 10,000 ϫ g for 5 min, the supernatant was loaded on a 12.5% SDS-PAGE gel by a reducing method.…”
Section: Western Blot Analysismentioning
confidence: 99%
“…The flow cytometric analysis procedure has been described previously (19). Briefly, the MA5.8 mutants were stained with an FITC-conjugated Armenian hamster anti-mouse CD3⑀ mAb (145-2C11; Coulter Immunology), an FITC-conjugated mouse anti-human mAb (TIA-2; Coulter Immunology), or a PE-conjugated rat anti-mouse Sdc1 mAb (281-2; BD Biosciences).…”
Section: Flow Cytometric Analysismentioning
confidence: 99%